2022
DOI: 10.1128/mbio.00431-22
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Compensatory Mutations Reveals the Importance of Electrostatic Interactions between HIV-1 Integrase and Genomic RNA

Abstract: In addition to its catalytic function, HIV-1 integrase (IN) binds to the viral RNA genome (gRNA) through positively charged residues (i.e., R262, R263, R269, K273) within its C-terminal domain (CTD) and regulates proper virion maturation. Mutation of these residues results in the formation of morphologically aberrant viruses blocked at an early reverse transcription stage in cells.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 105 publications
1
10
0
Order By: Relevance
“…Prior studies suggested that the formation of a core IN tetramer is relevant for the proper execution of two distinct functions mediated by IN, integration 9 and RNA binding 24,25,35 . We set out to determine the structure of the WT IN tetramer in apo form without nucleic acids bound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies suggested that the formation of a core IN tetramer is relevant for the proper execution of two distinct functions mediated by IN, integration 9 and RNA binding 24,25,35 . We set out to determine the structure of the WT IN tetramer in apo form without nucleic acids bound.…”
Section: Resultsmentioning
confidence: 99%
“…The arrangement of the tetrameric IN assembly has important implications for a working model of its binding to RNA. The four CTDs, which are crucial for RNA binding 24,25,35 , zigzag along the interface of two IN dimers ( Figure 6a ). These CTDs provide a highly positively charged surface stretching over 80 Å, which could effectively bind RNA ( Figure 6b ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the GagPol-containing IN:M50I/V151I may differentially regulate the ESCRT system and suppress virus release. Recent studies highlight accessory functions of matured IN (5254), IN stimulates RT (52), IN interacts with RNA(5456), acetylation of CTD of IN is associated with defects in proviral transcription (55). We now demonstrate a new potential role of IN domain in GagPol polyprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of HIV-1 RT products and 2-LTR circles was measured by qPCR using primers specific for early and late RT products (see above table). Extracted DNA was analyzed for accumulation of RT products, 2-LTR circles, and integration as described before ( 97 , 98 ).…”
Section: Methodsmentioning
confidence: 99%